Analisis Komparatif Saham PT Tempo Scan Pacific Tbk dan PT Unilever Indonesia Tbk Tahun 2021-2023 dengan Rasio Fundamental - Febrianti Hasnah, Eicha; Nagita Syawalinda, Rara; Audina, Sandra (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
Tempo Scan Pacific (TSPC) and PT Unilever Indonesia Tbk (UNVR) in the 2021-2023 period, as well as comparing the financial performance of the two to provide a clear picture of investment prospects. The analysis results show that PT Tempo Scan Pacific has a more stable performance with a consistent increase in EPS and a relatively low DER, indicating a healthier financial position. In contrast, PT Unilever Indonesia experienced a continuous decline in EPS and had a high DER, indicating a large dependence on debt to finance operations. Even though Unilever's PER is higher, which indicates an expensive share valuation, declining financial performance and the issue of a boycott of Unilever open up opportunities for TSPC to gain market share. Based on the analysis results, PT Tempo Scan Pacific is more attractive as an investment choice because it has greater growth potential, especially in the Indonesian domestic market, with the prospect of faster profits in the short term.